Quantifying edge influence on plant community structure and composition in semi‐natural dry grasslands. Issue 4 (20th August 2017) - Labadessa, Rocco; Alignier, Audrey; Cassano, Stefania; Forte, Luigi; Mairota, Paola
Abstract: Aims: We investigated the influence of anthropogenic boundaries on semi‐natural grassland plant communities in terms of: (1) depth and magnitude of edge influence and (2) changes in plant community composition associated with boundary attributes. Location: Alta Murgia, Puglia, southeast Italy. Methods: Sampling sites were selected taking into account three boundary attributes thought to be most important in the study area, i.e. adjacent land use, presence/absence of stone wall at the patch boundary and occurrence of slope. Plant communities were surveyed along 40‐m transects perpendicular to the patch boundary. Each transect was divided in six plots at given distances from patch boundary. Data were collected related to a set of plant community descriptors referring to structure, composition, life history traits and ecological attributes. A novel methodology that relies on the definition of inner plots as relative interior habitat was introduced for assessment of the depth and magnitude of edge influence. DCA was then used to characterize edge communities. Results: Significant edge influence on grassland plant communities was limited to the adjacent boundary (<2.5 m). For the majority of descriptors, magnitude of edge influence was higher in grasslands adjacent to crops rather than to roads, in sloping rather than flat edges, and in wall‐bounded rather than unbounded patches. Plant assemblages dominated by either ruderal species or xerothermic grassland species were, in all cases, associated with unbounded edges, while distinct assemblages were observed in wall‐bounded plots according to their different morphology. Wall‐bounded sloping edges were characterized by woodland species, whereas their non‐sloping analogues were associated with calcareous grassland species. Conclusions: Our findings provide new insights into the influence of anthropogenic boundaries on semi‐natural dry grassland by assessing the depth and magnitude of edge influence, as well as the changes in composition of edge plant communities as a function of the combination of boundary attributes. While the method implemented enabled us to address many of the issues experienced in quantification of edge influence in herbaceous communities, it also allowed us to demonstrate the major role of boundary attributes in modulation of edge community patterns. Abstract : The influence of anthropogenic boundaries on semi‐natural dry grasslands was assessed by means of a new comparative approach. Edge influence was significant at the boundary adjacencies only, while changes in its magnitude and in plant community composition were modulated by the combination of boundary attributes, which should be taken into account when planning land modifications and local management actions.